Decomposition of the Determinants of Return on Equity (ROE) in the Indonesian Insurance Industry: Implementation of the Du Pont Method - Zalukhu, Kasieli; Palupiningtyas, Dyah (PT. Riset Press International, 2025)
This study uses a modified Du Pont decomposition approach to analyse the determinants of Return on Equity (ROE) in the Indonesian insurance industry. The research was conducted on PT Asuransi Ramayana Tbk and PT Asuransi Jasa Tania Tbk for the 2022-2023 period, focusing on the identification and analysis of the components forming ROE. The research methodology employed a descriptive quantitative approach with a modified Du Pont analysis to accommodate the specific characteristics of the insurance industry. The findings reveal significant differences in the ROE performance of the two companies. PT Asuransi Ramayana Tbk recorded an ROE of 13.08% in 2023, supported by better operational efficiency (combined ratio of 78.76%) and a significant increase in investment returns (investment yield of 9.42%). Meanwhile, PT Asuransi Jasa Tania Tbk improved ROE from 0.18% to 1.24%, primarily driven by an increase in net profit margin from 0.35% to 2.11%. The decomposition analysis identified three key factors influencing ROE: operational efficiency, as reflected in the combined ratio; investment management effectiveness, as seen from the investment yield; and capital structure optimisation, indicated by financial leverage. These findings provide a systematic framework for insurance company management to optimise economic performance and for regulators to develop policies that support the industry's sustainability.